PROTECTION AGAINST PLANT PESTS BASED ON RESISTANT WHEAT VARIETIES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article explores various types of wheat contaminated with wheat juice in a plant protection laboratory. As a result, the durability of various wheat varieties was evaluated and relatively stable varieties were determined.